Persepsi Wisatawan Terhadap Komponen Daya Tarik Wisata Pantai Sasak Pasaman Barat - Nurul Azizah; Idea Alvira (Institut Seni Indonesia Padangpanjang, 2026)
This study was motivated by the importance of understanding touristâ€™ perceptions of tourism destinations is essential for evaluating and improving destination management. Sasak Beach is the one of the tourist destinations in West Pasaman Regency that possesses various tourism attractions, accessibility, and amenities. This study employed a quantitative descriptive method. The population consisted of tourist visiting Sasak Beach, with a sampling technique used was accidental sampling. Data were collected through questionnaires, observation, and documentation. Data analysis was conducted using descriptive statistic, including frequency, percentage, and mean scores with the assistance of SPSS software. The results indicate that the attraction, accessibility, and amenities dimensions achieved mean scores of 3,13, 3,18, and 3,04, respectively, all of which fall within the agree category. Overall, touristsâ€™ perceptions of Sasak Beach achieved a mean score of 3.14, which falls into the agree category.Â These findings suggest that tourists generally have positive perceptions of Sasak Beach. However, improvements in environmental cleanliness, public facilities, and directional signage remain necessary to enhance destination quality.